Quantitative results for perturbed stochastic differential equations. (1996) - Stoyanov, Jordan; Botev, Dobrin
Abstract : The paper is devoted to Itô type stochastic differential equations (SDE's) with small perturbations. Our goal is to present strong results showing how close are the 2 m -order moments of the solutions of the perturbed SDE's and the unperturbed SDE.